Psychological Aspects of Responding to Feedback in the Coaching Process - Agnieszka Fornalczyk (University of Lower Silesia, 2013)
The article discusses ways in which individuals respond to feedback received in the coaching process. In the first part, the author discusses different response styles to feedback and their consequences. She focuses especially on the defensive, dominating, manipulative, and improvement-oriented behaviors of the coached. In the second part, she addresses psychological determinants of effective feedback reception by the coaching participants, including their dispositional determinants. The author concludes emphasizing that for the coached to correct their behavior, the provision of feedback by coaches must be founded on the knowledge of the mechanisms and the dispositional determinants of human functioning.